2011
DOI: 10.1177/230949901101900127
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty for Pigmented Villonodular Synovitis of the Shoulder: A Report of Two Cases

Abstract: Pigmented villonodular synovitis is a reactive condition characterised by exuberant proliferation of synovial villi and nodules. It may be localised or diffuse and can cause severe articular damage. This report is of 2 patients with pigmented villonodular synovitis of the shoulder causing extensive arthritic changes. Both patients underwent shoulder hemiarthroplasty and total synovectomy and achieved satisfactory painless range of motion, with no signs of local recurrence or loosening of the prosthesis after 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Various intra-articular and extra-articular sites of origin including specific bursa locations have been identified. The knee is the most commonly affected joint, but rare cases of shoulder joint involvement have been reported [2][3][4][5]7,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various intra-articular and extra-articular sites of origin including specific bursa locations have been identified. The knee is the most commonly affected joint, but rare cases of shoulder joint involvement have been reported [2][3][4][5]7,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…However, benign soft tissue tumor progression about the shoulder also has consequences. The permanent erosion of bone, joint and soft tissue structures, as well as, progressive rotator cuff tears and neurovascular invasion have been documented [2][3][4][5][6][7][8][9][10][11]. The result of this destruction leads to increasing disability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]11 A total of 2 cases published in 1 report were treated by hemiarthroplasty with total synovectomy. 5 Recurrence of PVNS is likely due to incomplete synovectomy. Johansson et al 2 reported a recurrence rate of 33%, whereas Byers et al 6 found a 50% recurrence after total synovectomy in diffuse PVNS.…”
Section: Discussionmentioning
confidence: 99%
“…Total shoulder arthroplasty and hemiarthroplasty, in which removal of the humeral head is performed, provide better access to the joint than the more conservative approaches. 4,5 Controversy exists regarding whether hemiarthroplasty or total shoulder arthroplasty is superior for the management of glenohumeral osteoarthritis. Despite this controversy, a general consensus exists that the outcome of total shoulder arthroplasty is much better than that of hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation